Embracing diversity and inclusivity in nursing: challenges and opportunities for transgender and intersex individuals in Pakistan - Noureen Fazal; Amjad Ali (Journal of the Pakistan Medical Association, 2024)
Variety is an integral aspect of our world, adding beauty and enabling us to appreciate the diverse qualities present in different aspects of life. Imagine a world without diversity, where we are left with only one type of fruit, flower, or colour. Such uniformity would render life bland and monotonous. Hence, the importance of diversity cannot be overstated, as it brings vibrancy and richness to our existence, making it essential for our well-being. God created diverse sexes, including female, male, intersex, and transgender individuals, each with roles to fulfil. However, intersex and transgender people often face barriers to healthcare access, professionals’ unfamiliarity with relevant terminology, failure to respect patients’ preferred pronouns, and treatment in non-inclusive environments [1]. Similarly, a 2024 study by Nation, Austin found that LGBT individuals often face fear, stigma, discrimination, homophobia, and even violence when seeking healthcare and mental health services [2]. Transgender individuals are underrepresented in nursing worldwide, including in Pakistan, due to fears of discrimination and social rejection, despite the profession’s esteemed status. Pakistan is grappling with a severe shortage of nurses, as evidenced by the 2022-23 report from the Pakistan Nursing Council, which indicates a total enrolment of 103,821 registered nurses. In the Asian region, there has been a notable increase in the departure of nursing professionals as a result of stress, burnout, and disproportionate workloads both proceeding and during the COVID-19 pandemic [3]. To address the nursing shortage, the transgender and intersex community’s potential should be recognized, given their physical and mental strength. Historically, they held roles like guards and chamberlains in the Middle East and China [4]. Transgender individuals, known for their compassion and empathy, are ideal for nursing roles. Integrating them helps address the nursing shortage, provides dignified opportunities, and reduces involvement in unethical activities like sex work and begging. Nurses should explore how to integrate transgender and intersex individuals into the profession with respect and dignity, considering eligibility, educational gaps, cultural objections, and workplace readiness. Rigorous research is needed to address these issues and ensure equal rights for all.